La2O3/CaO CATALYSTS AND ITS APPLICATION IN THE OXIDATIVE COUPLING OF METHANE - Garrido-Schaeffer, A. (1998)
La2O3/CaO catalysts were prepared at different weight percentages of La2O3.Por the coprecipitation method described porRaO, CaCO3 is prepared and then it was impregnated in a solution of La (NO) 3.6H2O thus obtaining the catalyst precursor . precursors dried at 393K and calcined at 973K, obtaining 0-15% La2O3/CaO catalysts. XRF elemental qualitative analysis was performed. By FTIR carbonates adsorbed species was observed. The presence of La2O3 and CaO phases was confirmed by XRD and BET surface area of the catalyst giving values ​​less than 9m2 / g The measurement of the activity for La2O3/CaO cataluzador 15% was measured, it was performed in a microreactor quartz, using a feed rate of methane / oxygen ratio of 4:1 and the reaction temperatures of 923, 973 and 1023 K, resulting in a maximum conversion temperature of 1023K of 26.84% methane conversion and selectivity to C2 + of 38.17%.